2016
DOI: 10.1007/s10751-016-1223-7
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of the magnetocaloric compound AlFe2 B 2

Abstract: The crystal and magnetic structures of AlFe 2 B 2 have been studied with a combination of X-ray and neutron diffraction and electronic structure calculations. The magnetic and magnetocaloric properties have been investigated by magnetisation measurements. The samples have been produced using high temperature synthesis and subsequent heat treatments. The compound crystallises in the orthorhombic crystal system Cmmm and it orders ferromagnetically at 285 K through a second order phase transition. At temperatures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In alignment with the experimental reports of Lu and co-workers [42] Magnetic data shown in Figure 5 indicate that within the (ac) plane of the 1-2-2 compound, the unit cell a-and c-axes are the easy and hard direction of magnetization, respectivelyan observation that is consistent with results derived from recent neutron scattering experiments [31] and computational calculations [34]. In agreement with calculated MAE values using electron FP-LMTO methods (see Table II), the measured magnetic anisotropy energy in the ac-plane is K~0.9…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In alignment with the experimental reports of Lu and co-workers [42] Magnetic data shown in Figure 5 indicate that within the (ac) plane of the 1-2-2 compound, the unit cell a-and c-axes are the easy and hard direction of magnetization, respectivelyan observation that is consistent with results derived from recent neutron scattering experiments [31] and computational calculations [34]. In agreement with calculated MAE values using electron FP-LMTO methods (see Table II), the measured magnetic anisotropy energy in the ac-plane is K~0.9…”
Section: Discussionsupporting
confidence: 90%
“…The ferromagnetic AlFe 2 B 2 system is comprised entirely of earth-abundant, non-toxic elements with a tunable magnetic transition temperature T c near room temperature [23][24][25][26] and is reported to exhibit ∆S mag values in the range 2.1 -4.4 J•kg -1 K -1 at μ 0 H = 2 T [23][24][25][26][27][28][29][30][31][32][33]; these values have been reported from polycrystalline specimens of uncertain isotropy. Neutron diffraction and Mössbauer experiments reveal that the magnetic moments in AlFe 2 B 2 are oriented along the crystallographic aaxis [24,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recently studied material system for magnetic cooling is AlM 2 B 2 (M = Fe, Mn, Cr), based on AlFe 2 B 2 [8][9][10][11][12][13][14][15]. The structure of AlFe 2 B 2 is orthorhombic (space group Cmmm) with (Fe 2 B 2 )-slabs in between layers of aluminium stacked along the b-axis [8].…”
Section: Introductionmentioning
confidence: 99%
“…The unit cell contains two formula units with the aluminium atoms occupying the 2a position and the iron and boron atoms occupying the 4i and 4 j positions, respectively. The unit cell parameters are 2.9233 (10), 11.0337 (14), and 2.8703(3) Å for a, b, and c, respectively. Previous studies have shown that the compound is ferromagnetic with an ordering temperature (T C ) around 300 K and magnetic moments close to 1 µ B /Fe-atom [9][10][11].…”
Section: Introductionmentioning
confidence: 99%